(3GdJdNjU aj JaSjQ GdbQBf GdYRjR QhGjI EHQGgje Hf eMeO GdLhjfjs - (3GdchGTj, GdehUdj, CHh GdYHGS, ehab GdOjf, CMeO Hf jhSa Hf GdMSf Hf QGaY, J (B680(3g`s ((3CMeO Hf EdjGS GdMGaX GdYfbQjs)
(3ChdgG (B:s
(3aj ChdgG ecJhH Cfg GdfUa GdChd ef JHUQI GdeJPcQ hJPcQI GdeJHUQ, JCdja ehab GdOjf CHi GdYHGS CMeO GdchGTj, hgPG NWCs
(3BNQgG (B:s
(3aj BNQgG eWGdYI d`(B: (3OhO Hjf Hjf Ce GdfcjSGQjs
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs